Using ecohydrology to predict algal biomass in the Raisin River watershed, (ON Canada) - Woods, Lieserl M. E (University of Ottawa (Canada), 2009)
The effects of groundwater and environmental variables on river ecology in terms of algal biomass (benthic and suspended) were determined across a watershed dominated by agricultural land-use (Raisin River, eastern Ontario). At the watershed scale, during summer base flows, light and temperature or Strahler stream order predicted suspended algal biomass (estimated by chlorophyll a) whereas turbidity and temperature predicted epilithic periphyton biomass in riffle zones; nutrients did not correlate with either algal community. Benthic algal biomass was negatively correlated with suspended algal biomass. At the reach scale, periphyton biomass and total phosphorus were temporally linked but the relationship became uncoupled by spates. Evidence for shallow hyporheic flow but not deep groundwater discharge was reported for one of two reaches studied. Benthic algal biomass accrual increased linearly with both a positive or negative hydraulic gradient, indicating that surface water/groundwater interactions were important.
Keywords: Hydrology.; Biology, Microbiology.